EFFECTIVENESS OF THE NEW ANTIMICROBIAL AGENT CEFINEL IN THE TREATMENT OF RESPIRATORY DISEASES IN PIGS - Музика, В. П.; Стецько, Т. І.; Падовський, В. Н.; Пашковська, М. В.; Голобородько, Т. О. (Scientific Progress & Innovations, 2013)
The results of the studies of microorganisms’ sensitivity, pathogens of respiratory diseases in pigs to cephalosporin antibiotic of the III generation of ceftiofur were showen. The obtained results showed a high sensitivity of bacterial isolates, allocated from diseased pigs, to this antimicrobial agent. Testing in a production environment of a new antimicrobial agent Cefinel, the active substance of which is ceftiofur showed its high therapeutic efficacy in the treatment of respiratory tract infections of bacterial etiology in pigs.